Preliminary observations on the reception of Flavius Josephus in Byzantine historical writings: the accounts of John Zonaras, Niketas Choniates and Michael Kritovoulos - KAMPIANAKI, Theofili (Byzantina Symmeikta, 2018)
no abstract available in English